Modulation transfer function in the analysis of electro-optical system performance - Pađen, Nedeljko; Perić, Dragana; Livada, Branko; Milosavljević, Milan (Vojnotehnički glasnik / Military Technical Courier, 2020)
Introduction/purpose: The Modulation Transfer Function (MTF) is a useful tool for an imaging system performance analysis. It is used in Electro-Optical (EO) system design, verification of targeted system parameters, but also in optimization  tasks for systems under test. This methodology based on the linear systems theory allows the performance analysis of complicated EO systems to be divided into subsystems. In this paper, the MTF methodology will be presented and explained, followed by the measurements performed in the electro-optical laboratory. The MTF measurements were performed on three types of cameras in different spectral bands, after which the results were compared to the model expectations and theoretical limits for the imaging system. For one of the sensors, the limiting frequency was also measured using the USAF 1951 test target which allowed the comparison between the methods. Methods: Laboratory measurements and theoretical mathematical calculations.Results: Based on the laboratory and theoretical results, the measurement results were further analyzed. Conclusion: The measurements have proven that the calculated cutoff frequency and the MTF curve represent the limit for the real measured system performance. Therefore, this study has confirmed that the MTF can be convenient for finding system limitations and bottlenecks and for increasing the overall performance of the system.
Keywords: MTF-Modulation Transfer Function; USAF 1951 test; electro-optics